Does solar energy reduce poverty or increase energy security? A comparative analysis of sustainability impacts of on-grid power plants in Burkina Faso, Madagascar, Morocco, Rwanda, Senegal and South Africa. (May 2022) - Brunet, Carole; Savadogo, Oumarou; Baptiste, Pierre; Bouchard, Michel A.; Cholez, Céline; Rosei, Federico; Gendron, Corinne; Sinclair-Desgagné, Bernard; Merveille, Nicolas
Abstract : See example https://www.sciencedirect.com/science/article/pii/S0022314X09002509?via%3Dihub Abstract: The United Nations has identified 17 Sustainable Development Goals (SDGs) that need to be addressed to ensure a peaceful and sustainable existence for all living species on planet earth. To a large extent, the SDGs are interconnected, so that addressing one can simultaneously influence another; here, we explore the role of photovoltaic energy technology in combating climate change and its potential advantages in alleviating poverty in six African countries. In this context, photovoltaic solar power plants which produce "green" electrical power from solar radiation may contribute to the achievement of several of these goals. This article analyzes the extent to which the operation of on-grid solar power plants found in Burkina Faso, Madagascar, Morocco, Rwanda, Senegal, and South Africa is a vector for sustainable development. Our results give us the opportunity to identify the role of governments in enhancing solar PV sustainability for poverty alleviation. Our methodology is both qualitative and quantitative. We pursued six case studies, performed a thorough grid analysis (seven categories of impacts analyzed at local, regional, national, and international levels), and defined a sustainability index specific to solar power plants. According to the sustainability model derived from our results based on contextual and structural variables, we found that, unless appropriate adjustments are made, grid-connected photovoltaic solar power plants have a limited impact on sustainable development and poverty abatement, especially at the local level. Video: For a video summary of this paper, please visit: https://www.polymtl.ca/magi/en/research-presentation-carole-brunet-phd .